Trinidad and Tobago : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This paper analyzes the historical and current energy booms of Trinidad and Tobago, and points out the main policy issues during boom times. It provides practical suggestions on the long-term management of the expected resource windfall in Trinidad and Tobago, and outlines theoretical guidelines to calculate sustainable consumption out of energy wealth and targets sustainable levels of non-energy fiscal deficits. It discusses the developments, main policy issues in the state-owned nonfinancial enterprise sector, and the proposed restructuring plan for the state sugar company. It also provides a Statistical Appendix for Trinidad and Tobago.